The Performance of the Health Communication Assessment Tool© (HCAT-f) in Calibrating Different Levels of Nurse Communication Skills in a French-Speaking Context - Anh Nguyet Diep; Jean-Christophe Servotte; Nadia Dardenne; Sophie Vanbelle; Vanessa Wauthier; Méryl Paquay; Suzanne Hetzel Campbell; Jonathan Goffoy; Anne-Françoise Donneau; Alexandre Ghuysen (University of Zurich, IKMZ - Department of Communication and Media Research, 2022)
Communication skills training is essential in nurse education. Miscommunication may lead to adverse events and unsafe healthcare. To date, valid and reliable instruments to serve both communication training and assessment purposes across different cultural contexts are scarce. The present study empirically tested a French-language version of the Health Communication Assessment Tool© (HCAT-f) across different levels of communication skills performance to establish its reliability and validity through a cognitive fluency framework. Ten experts in communication and 52 nurse educators rated three videos simulating conversations between a nurse and a patient scheduled for lumpectomy. Each video captured a different level of communication skills performed by the nurse: High, medium, and low. Three distinct constructs were identified, i.e., professional presentation, empathy, and trust building. At absolute single-measure, an ICC = .43 suggested adequate interrater reliability of the whole scale for the medium-performed scenario, which decreased in low-performed (ICC = .35) and high-performed (ICC = .18) scenarios. The HCAT-f fulfils the criteria of linguistic equivalence, contextual relevance, and demonstrates acceptable construct validity. It can be used as a summative assessment tool after prior training on scale calibration is in place because interrater agreement was difficult to be established in high and low performance scenarios.